2013
DOI: 10.1002/pat.3153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and anticorrosive properties of poly(2,3‐dimethylaniline)/nano‐Al2O3 composite synthesized by emulsion polymerization

Abstract: Poly(2,3-dimethylaniline)/nano-Al 2 O 3 composite (PAC) was synthesized by emulsion polymerization using dodecyl benzene sulfonic acid as emulsifier and dopant. The structure of PAC was characterized by Fourier fransformation infrared spectroscopy, UV-visible adsorption spectroscopy, and field emission scanning electron microscopy. The thermal stability was studied by thermogravimetric analysis, and the electrochemical performances were studied by cyclic voltammetry measurements. Epoxy coatings containing PAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It is well known that the ring substituted modification of PANI usually can improve the solubility, conductivity, thermal stability, and corrosion resistance of PANI derivatives [16]. Bilal et al [17] and our group [18] have confirmed the excellent structure and corrosion resistance of poly(o-toluidine).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is well known that the ring substituted modification of PANI usually can improve the solubility, conductivity, thermal stability, and corrosion resistance of PANI derivatives [16]. Bilal et al [17] and our group [18] have confirmed the excellent structure and corrosion resistance of poly(o-toluidine).…”
Section: Introductionsupporting
confidence: 56%
“…These results indicate that the assembled outer polymer films can effectively protect the SiC/Zn surface and that the POT film is more protective. The improved corrosion protection ability of the composite coating is derived from the physical and electronic barrier effects of conducting polymers [12,16]. The poly(o/m-toluidine) was similar to PANI, exhibiting a redox potential close to silver, which could ennoble the available zinc surfaces and form one or more layers of passive oxide films on the surface of the SiC/Zn coating.…”
Section: Corrosion Resistances Of Electrodeposited and Bilayer Coatingsmentioning
confidence: 99%
“…observed that the epoxy/polyamide coatings modified with 3.5 wt.% Al 2 O 3 nanoparticles showed optimal barrier properties, compact structure and resistance ability against hydrolytic degradation [118] . Rout, [119] Li [108b] and Babaei‐Sati et al. reported the similar role of Al 2 O 3 in the alumina/polymer nanocomposite coating with significant anticorrosive performance.…”
Section: Polymer Nanocomposite‐based Coatings For Corrosion Protectionmentioning
confidence: 84%
“…Rout [123], Li [124], and Babaei-Sati et al all found that Al 2 O 3 plays a similar role in alumina/polymer nanocomposite coatings with strong anticorrosive properties. Because of their high chemical activity and surface energy, Al 2 O 3 has a limited potential as a reinforcement due to poor dispersion of the nanofillers and the tendency of NPs to coalesce [125][126][127]. Surface modification of Al 2 O 3 NPs, such as chemical surface functionalization using silane coupling agents and surfactant grafting, is a viable method for addressing this problem [128,129].…”
Section: Nano-al 2 Omentioning
confidence: 99%